2016
DOI: 10.1080/2162402x.2016.1261778
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of tumor growth and metastasis by EMMPRIN multiple antigenic peptide (MAP) vaccination is mediated by immune modulation

Abstract: Previously, we have identified a new epitope in EMMPRIN, a multifunctional protein that mediates tumor cell-macrophage interactions and induces both MMP-9 and VEGF. Here, we synthesized this epitope as an octa-branched multiple antigenic peptide (MAP) to vaccinate mice implanted with subcutaneous syngeneic colon (CT26), prostate (TRAMP-C2) or renal (RENCA) cell line carcinomas. Vaccination inhibited, and sometimes regressed, tumor growth in a dose-dependent manner, reaching 94%, 71% and 72% inhibition, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 42 publications
0
27
0
Order By: Relevance
“…In addition, nitrites were accumulated in tumors receiving the combined stimulation, suggesting a shift in macrophage activation. We have recently shown that TGFβ is the dominant cytokine in the RENCA TME ( 41 , 42 ). Therefore, its reduced levels together with the increased macrophage production of NO, altered the TME, alleviated immune suppression and allowed CD8 + T cells to infiltrate deep into the tumor and eradicate tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, nitrites were accumulated in tumors receiving the combined stimulation, suggesting a shift in macrophage activation. We have recently shown that TGFβ is the dominant cytokine in the RENCA TME ( 41 , 42 ). Therefore, its reduced levels together with the increased macrophage production of NO, altered the TME, alleviated immune suppression and allowed CD8 + T cells to infiltrate deep into the tumor and eradicate tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 Here we show that 161-pAb and complement are sufficient to induce regulated necrotic death that resembles necroptosis. Because necroptosis has been associated with induction of ICD,42 and based on our previous results, we propose that the 161-pAb with complement can induce ICD in vivo.…”
mentioning
confidence: 71%
“…Manuscript to be reviewed presentation on MHC I and II molecules and enhance their immunogenicity, these vaccines continue to fail to demonstrate adequate efficacy or improve the overall survival rate (Simanovich et al, 2017). To solve this problem, epitopes can be displayed on a multiple antigenic peptide (MAP) system which contains a core matrix of lysine residues that form a scaffold (Tam, 1988).…”
Section: Vaccines Multiple Antigenic Peptide (Map)mentioning
confidence: 99%
“…The results showed that the three HCV envelope MAP peptides exhibit strong immunogenicity and produce higher levels of neutralizing antibodies (Abdelhafez et al, 2017). Tumor vaccines based on MAP may also be an effective way to treat and prevent certain types of cancer (Simanovich et al, 2017).…”
Section: Vaccines Multiple Antigenic Peptide (Map)mentioning
confidence: 99%